Promoting infection prevention behaviors in family caregivers of preschoolers with acute lymphoblastic leukemia: the application of self-care deficit theory: 10.55131/jphd/2022/200114 - Lamtrakul, Su-ari; Yunibhand, Jintana; Chaiyawat, Waraporn (Journal of Public Health and Development, 2022)
The infection prevention behaviors of family caregivers are critical for the survival of preschoolers with acute lymphoblastic leukemia. As a result, nurses must devise an effective strategy for encouraging family caregivers to engage in these behaviors. The purpose of this quasi-experimental, pretest-posttest design was to compare infection prevention behaviors between family caregivers of preschoolers with acute lymphoblastic leukemia who received the infection prevention behavior program (PPIPB) and those who received conventional nursing care. Forty-five family caregivers of preschoolers with acute lymphoblastic leukemia were selected, of which 23 were assigned in an experimental group who received conventional nursing care and 22 in a control group who received the PPIPB. The intervention, which was based on the Self-Care Deficit Theory, aimed to enable the potential of the dependent-care agency regarding infection prevention behaviors of family caregivers. On the first and twelfth days of the study, all family caregivers were assessed for infection prevention behaviors using the Infection Prevention Behaviors Questionnaires (IPBQ). At the statistical level of .05, the experimental group’s mean difference scores for infection prevention behaviors (Mean=4.78, SD=3.93) were significantly higher than those in the control group (Mean=0.64, SD=0.73). The efficacy of the nursing intervention based on Self-care Deficit Theory was demonstrated in this study. The theory was used to successfully improve family caregivers’ infection prevention behaviors for preschoolers with acute lymphoblastic leukemia.